2012
DOI: 10.12669/pjms.291.2595
|View full text |Cite
|
Sign up to set email alerts
|

To differentiate benign from malignant thyroid nodule comparison of sonography with FNAC findings

Abstract: Objectives: To evaluate the diagnostic accuracy of sonography and Fine Needle Aspiration Cytology (FNAC). Methodology: This follow-up study was approved by review board and conducted at Endocrine Clinic and Radiology Department of Imam Reza, Kermanshah. The patients were diagnosed to have thyroid nodule examined by FNA and Sonography suspicious malignant cases underwent surgery. Results were entered in SPSS 11.5 chi-Square and Fisher exact test applied to compare malignant and benign nodule characters. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
1
12
1
3
Order By: Relevance
“…The present findings differed from that of a previous study, which concluded that on diameter comparison, no significant association was found between malignancy and a nodule size of >15 mm using FNAB (20). The higher incidence of microcarcinoma in the present study and timely surgery on suspected carcinomas may contribute to the difference in conclusions.…”
Section: Discussioncontrasting
confidence: 99%
“…The present findings differed from that of a previous study, which concluded that on diameter comparison, no significant association was found between malignancy and a nodule size of >15 mm using FNAB (20). The higher incidence of microcarcinoma in the present study and timely surgery on suspected carcinomas may contribute to the difference in conclusions.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our findings, earlier studies showed a significant correlation between FNA cytology findings of suspicious malignancy and the final diagnosis [13,31]. Therefore, US-FNA findings of suspicious malignancy could be utilized for considering the need and extent of surgical intervention [32].…”
Section: Discussionsupporting
confidence: 90%
“…They are found in 4%-8% of adults by means of palpation, in 10%-41% by means of US (Carroll et al, 1982;Brander et al, 1991;Bruneton et al, 1994;Wiest et al, 1998;Nam-Goong et al, 2004;Rahimi et al, 2013) and in 50% by means of pathologic examination at autopsy. The prevalence of thyroid nodules increases with age.…”
Section: Discussionmentioning
confidence: 98%